Effects of laparoscopy and laparotomy on stress and hemodynamics in experimental sepsis model in rats (Annals of Medical Research, 2021)
Aim: Laparoscopic abdominal surgery leads to reduced inflammatory response compared with laparotomy. However, there is controversial approaches are present in abdominal diseases complicated by diffuse or localized peritonitis. Materials and Methods: Experimental cecal ligation and puncture method is used in the study. A total of 24 rats were used in the study. We divided all rats randomly four groups: control, sepsis, laparotomy and laparoscopy. After sepsis model was applied, we took blood samples and lung and liver samples as well. In plasma samples we determined 8-OHdG, 3-Nitrotyrosine, HNE, PGF-2α via ELISA methods. The tissue samples were analyzed since the amount of blood samples were inadequate in all subjects. We measured MPO activity to assess the neutrophil infiltration rates. Results: 3-NT mean values in laparotomy and laparoscopy groups were found to be almost the same while the difference between sepsis and laparoscopy groups was statistically significant (p =0.015) and decreased in the group undergoing laparoscopy. MPO levels obtained in rats underwent laparoscopy in liver tissue were found to be lower when compared with control and laparotomy groups and the difference between them was statistically significant. Also, MPO levels was found higher in sepsis laparotomy model as compared sepsis laparoscopy models.Conclusion: Laparoscopy is accepted as golden standard in several elective procedures, since it is less stressful. Our results indicate that laparoscopy is superior to laparotomy in terms of inflammatory response in sepsis and should be preferred in septic patients.
Keywords: Laparoscopy; laparotomy; oxidative stress; sepsis